Converting and expanding a mobile support intervention: Focus group and field-testing findings from individuals in active tuberculosis treatment. (April 2020) - Iribarren, Sarah J.; Rodriguez, Yvette; Lin, Lorelei; Chirico, Cristina; Discacciati, Vilda; Schnall, Rebecca; Demiris, George
Abstract: Background: Non-adherence to tuberculosis (TB) treatment jeopardizes the individual's health and contributes to disease transmission and drug resistance. New patient-centered strategies are needed to improve TB treatment outcomes. Purpose: To convert and expand a texting-based intervention into a mobile optimized application (app), evaluate the feasibility of an added self-administered paper-based drug metabolite test, and identify needs and preferences to inform their iterative design. Methods: Qualitative methods using focus groups and field testing with patients in active TB treatment were used to gather initial input on the converted intervention design, content and issues using at home test strips to report medication adherence. Seven participants were recruited from an outpatient clinic within a regional public reference hospital specialized in respiratory diseases in Argentina. Thematic analyses were conducted on the transcripts and session notes. Results: Participants considered interactive communication, access to answers to frequently asked questions, and tracking of progress in treatment as important. Participants reported having many questions and uncertainties at initiation of treatment and emphasized a need for reliable information, assurance and support from both providers and peers. Other suggestions included streamlining the graphical user interface for easier and shorter data entry times and usability. Conclusions: Overall feedback from the participants regarding the intervention was positive, reporting that it was useful and relevant, and they were eager to contribute their ideas for improvement and additional functionality. Valuable feedback to improve functionality and meet the needs of end-users were obtained to inform the generation of new design ideas for refinement and testing in a pilot study.